2011
DOI: 10.1002/pmic.201000319
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomics analysis to identify a glycoform on haptoglobin associated with lung cancer

Abstract: Glycosylation is a common protein modification that is of interest in current cancer research because altered carbohydrate moieties are often found during cancer progress. A search for biomarkers in human lung cancer serum samples using glycoproteomic approaches identified fucosylated haptoglobin (Hp) significantly increased in serum of each subtype of lung cancer compared to normal donors. In addition, MS provided evidence of an increase of Hp fucosylation; the glycan structure was determined to be an α 2,6-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 37 publications
3
40
0
Order By: Relevance
“…Applying a similar 2D-gel proteomic strategy to our own to human sera, Comunale et al [39] identified 19 serum proteins that were hyperfucosylated in HCC, but also in cirrhosis and other liver diseases; however, a subsequent study showed that levels of fucosylated hemopexin and fetuin A were higher in HCC serum than in serum from patients with other liver diseases [40]. Fucosylated haptoglobin has also been reported as a potential biomarker in pancreatic cancer and lung cancer [41]. AAL is a commercially available lectin that is known for its high affinity for α-1,6-fucosylated oligosaccharides [42].…”
Section: Discussionmentioning
confidence: 94%
“…Applying a similar 2D-gel proteomic strategy to our own to human sera, Comunale et al [39] identified 19 serum proteins that were hyperfucosylated in HCC, but also in cirrhosis and other liver diseases; however, a subsequent study showed that levels of fucosylated hemopexin and fetuin A were higher in HCC serum than in serum from patients with other liver diseases [40]. Fucosylated haptoglobin has also been reported as a potential biomarker in pancreatic cancer and lung cancer [41]. AAL is a commercially available lectin that is known for its high affinity for α-1,6-fucosylated oligosaccharides [42].…”
Section: Discussionmentioning
confidence: 94%
“…A search for biomarkers using mass spectrometry in serum samples of human lung cancer patients' identified significantly increased levels of fucosylated Hp in each subtype of lung cancer as compared to controls, thus suggesting its role as a marker to monitor lung cancer progression [103]. Proteomic analyses have confirmed significant differences in concentrations of Hp β chain in sera of lung cancer patients vis-a-vis healthy individuals and patients with other types of solid tumors and respiratory diseases [104]. The Hp β chain seems to be useful in diagnosing lung cancer, but is not reliable enough as a sensitive or specific biomarker.…”
Section: Lung Cancer Protein Biomarkers In Serum: Current Statusmentioning
confidence: 88%
“…Meanwhile, previous studies have shown that the levels of Lewis-type (Fuc1, 3/4) fucosylation, in addition to core-fucosylation are also increased under inflammatory disease conditions such as cystic fibrosis and lung cancer [45,47,48]. It might therefore be possible that the Lewis-type fucose in serum SP-D might be simultaneously measured together with a core-fucose in the present assay because AAL also recognizes the Lewis-type fucose in addition to core-fucose [49] and that might lead to such high levels of fucosylation in serum SP-D in this study.…”
Section: Accepted Manuscriptmentioning
confidence: 99%